The relevance of financial and economic factors for determining banking risk across Europe - Renata Karkowska (Center for Social and Economic Research (CASE), 2017)
The goal of this study is to identify empirically how country-level development, taking into account the financial and macroeconomic environment, affect the risk profiles of the banking sector in Europe. Through a dataset that covers 3,399 European banks spanning the period 1996-2011, and the methodology of panel regression, the empirical findings document the heterogeneity of banking risk determinants. I examine the implications of bank leverage that manifest itself as spreading and growing instability. The study contributes to and combines the different strands of literature and understanding of the importance of the links between the variables. It also contributes to the literature by focusing on a group of countries from Central and Eastern Europe and the Commonwealth of Independent States that have not been studied before. The extended model provides a causal link between risk in the banking sector and the growth of the financial market and macroeconomy. I apply four measures of country-level development that are available in previous studies: share of foreign ownership in the banking sector; the financial freedom index; the real growth rate; and stock market capitalization. Using these measures, I obtain different results which highlight the fact that the effect of macroeconomic and financial development on banking sector risk-taking is ambiguous.
Keywords: F36; F65; G21; G32; G33; 330; banking risk; leverage; financial market; liberalization; economic growth; lending